Modified fs-Laser Inscribed FBG Array for Rapid Mode Shape Capture of Free-Free Vibrating Beams - Theodosiou, Antreas; Lacraz, Amédéé; Polis, Michael; Kalli, Kyriacos; Tsangari, Maria; Stassis, Andreas; Komodromos, Michael (My University, 2016)
We report on the development of a multiplexed sensor array of fiber Bragg gratings (FBGs), inscribed using a femtosecond laser, and its demonstration as a quasi-distributed sensor to capture the mode shapes, through surface displacement sampling, of a free-free vibrating beam. Our method is based on a plane-by-plane inscription approach, whereby a 2-D index change is written across the fiber core, controlling the width and depth of the modified region. This allows for the fast inscription of multiple wavelength FBGs in coated optical fibers, with the advantage of less stringent alignment requirements. The FBGs are multiplexed in the wavelength domain using a high-speed demodulator, using a fast, custom-made computational algorithm. We recover rapid and single-step wavelength- and time-dependent displacement information, extracting the first two mode shapes of a vibrating beam and their respective degrees of freedom resonance frequencies in <0.4 s.
Keywords: Bragg grating sensors; Surface displacement sampling; Femtosecond laser; Optical fiber sensors; Shape sensing